Poverty and social conflict in Sri Lanka : integrating conflict sensitivity into poverty analysis - Symposium on Poverty Research in Sri Lanka 2003 Colombo, Sri Lanka); Asirwatham, Ronnate; Thalayasingam, Prashan; Centre for Poverty Analysis (Sri Lanka); Program to Improve Capacities for Poverty Research; Sri Lanka Association for the Advancement of Science. Section F.; Great Britain. Department for International Development; Deutsche Gesellschaft für Technische Zusammenarbeit; Konrad-Adenauer-Stiftung. (Colombo : Centre for Poverty Analysis, Program for Improving Capacities for Poverty and Social Policy Research, 2004)
Papers presented at the seminar.
"Sponsored by Department for International Development, German Federal Ministry for Economic Cooperation and Development through German Technical Cooperation, Konrad-Adenauer-Stiftung."
"Annual symposium on poverty research in Sri Lanka, series no. 2-2004"--Addded t.p.
Keywords: Poor -- Sri Lanka -- Social conditions -- Congresses; Ethnic conflict -- Sri Lanka -- Congresses